Enhancing the performance of lead-free CsInCl3 perovskite solar cells with Ag and Au plasmonic nanoparticles: A DFT and SCAPS-1D analysis - Muhammad Zulqarnain Abbasi; Anees Ur Rehman; Muhammad Sheraz; Wajahat Ullah Khan Tareen; Muhammad Kaleem; Shayan Tariq Jan; Haider Ali; Teong Chee Chuah (Results in Engineering)
The search for non-toxic, high-efficiency perovskites has driven the development of innovative material engineering strategies. Due to the toxic nature of lead (Pb), extensive research has been conducted to identify alternative solutions. While these alternatives show outstanding potential, they have yet to match the performance levels of MAPbI3. This study presents a novel method to improve both the electrical and optical properties of CsInCl3 perovskite by adding Ag and Au plasmonic nanoparticles for the first time. We carefully examined the electronic, optoelectronic, and structural properties of doped CsInCl3 using first-principles Density Functional Theory (DFT) calculations and SCAPS-1D simulations. We computed all properties using the GGA-PBE exchange-correlation functional and USP (ultrasoft pseudo-potential). When Ag and Au were added to the indium site, the band gap decreased from 1.632 eV (pure) to 1.404 eV Ag-doped and 1.10 eV Au-doped. Optical properties, calculated across the photon energy range of 0–20 eV, revealed a redshift in the absorption edge for Ag-doped CsInCl3, while Au-doped CsInCl3 retained a similar absorption profile to the pure compound. The static refractive index increased from 1.96 for pure CsInCl3 to 2.04 and 2.17 for Ag and Au-doped compounds, respectively, indicating improved optical response. The combined effects of engineered absorption and doping on electrical solar cell parameters were investigated using SCAPS-1D simulations, achieving a power conversion efficiency (PCE) of ∼25.5 %, significantly higher than the ∼17.1 % observed for pure CsInCl3 perovskite material. These findings underscore the transformative potential of Ag and Au doping in tailoring CsInCl3 for high-performance optoelectronic and photovoltaic applications, marking a significant step toward the development of next-generation, non-toxic perovskite solar cells.